Assurance of Learning (AoL) documentation briefing session 2024 - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
On 27 August 2024, Assoc. Prof. Dr. Wahida Ahmad, Head of Postgraduate Studies, AAGBS, led an insightful Assurance of Learning (AoL) Documentation Briefing Session. The session brought together lecturers from AAGBS main campus and branch campuses, reflecting a strong commitment across the institution to maintain consistency and quality in academic delivery. The briefing focused on strengthening understanding of AoL documentation requirements, assessment alignment, and continuous improvement processes to ensure that the 2024 curriculum meets and upholds the highest standards of academic excellence and quality assurance. Through this session, participants were able to align teaching, learning outcomes, and assessment practices in support of AAGBS's ongoing efforts to enhance programme quality and accreditation readiness.